2018
DOI: 10.1016/j.urology.2018.01.037
|View full text |Cite
|
Sign up to set email alerts
|

80-W GreenLight Laser Vaporization Versus Transurethral Resection of the Prostate for Treatment of Benign Prostatic Obstruction: 5-Year Outcomes of a Single-center Prospective Randomized Trial

Abstract: Noninferiority of the GL PV to TURP was confirmed in all functional and safety outcomes at 5-year follow-up. GL-PV could be a safe surgical alternative for patients suffering from benign prostatic obstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…The predetermined search and selection criteria yielded 22 publications,2 7–11 24–39 reporting 19 separate clinical studies. Three studies (ie, Bachman et al ,10 29 Thomas et al 30) refer to an identical study, and two studies24 31 were from the same trials over different periods of time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The predetermined search and selection criteria yielded 22 publications,2 7–11 24–39 reporting 19 separate clinical studies. Three studies (ie, Bachman et al ,10 29 Thomas et al 30) refer to an identical study, and two studies24 31 were from the same trials over different periods of time.…”
Section: Resultsmentioning
confidence: 99%
“…Previous clinical studies have evaluated retrograde ejaculation rates, although conclusions could not be provided with any authority because findings were generally inconsistent and gathered over relatively short periods of time 7 10 25 27 38. The longest running RCT which compared PVP with TURP had a 60-month follow-up, and suggested there is similar improvement in IPSS, Qmax, PVR, QoL and IIEF 36 39…”
Section: Discussionmentioning
confidence: 99%
“…Finally, 14 papers were identified for metaanalysis. [12][13][14][15][16][17][18][19][20][21][22][23][24][25] Supplementary Figure 1 shows the PRISMA flow diagram of the study.…”
Section: Resultsmentioning
confidence: 99%
“…Liu reported that PKRP was superior to TURP in terms of serum sodium reduction, hospital stay, blood transfusion rate, TURS and urethral stricture incidence, while there was no significant difference in IIEF-5 or retrograde ejaculation 19 . Many studies have compared PVP with PKRP, indicating their efficacy and safety in the treatment of BPH 20 25 . However, studies comprehensively comparing their effects with adequate follow-up are lacking.…”
Section: Discussionmentioning
confidence: 99%